Innovation as a Key Success for Competitive Excellence Strategy in SMEs of Iraq - Almrshed, Sattar Kadim Hachim; Alaboody, Ali Abd Al Razaq; Jundi, Muslim Jabbar (South Asian Journal of Social Sciences and Humanities, 2024)
The paper tests the influence of innovation on competitive excellence strategy in detergent and soap SMEs in Iraq. The study is a cross-sectional. The researchers used a random sampling to collect the data. The sample size was of 390. Finding show that the influence of innovation on the “competitive” excellence strategy is positive and significant, the results show that SMEs would finance in innovative activities to improvement competitive advantage. Further, the study proposes that this framework should investigate the effect of innovation on competitive excellence strategy in other cont6ext of Iraqi SMEs. The limitation and future recommendation are discussed in the end.